Composition characterization and biotransformation of dissolved, particulate and algae organic phosphorus in eutrophic lakes. (October 2020) - Feng, Weiying; Yang, Fang; Zhang, Chen; Liu, Jing; Song, Fanhao; Chen, Haiyan; Zhu, Yuanrong; Liu, Shasha; Giesy, John P.
Abstract: Characteristics and transformation of organic phosphorus in water are vital to biogeochemical cycling of phosphorus and support of blooms of phytoplankton and cyanobacteria. Using solution 31 P nuclear magnetic resonance (NMR), combined with field surveys and lab analyses, composition and structural characteristics of dissolved phosphorus (DP), particulate phosphorus (PP) and organic P in algae were studied in two eutrophic lakes in China, Tai Lake and Chao Lake. Factors influencing migration and transformation of these constituents in lake ecosystems were also investigated. A method was developed to extract, flocculate and concentrate DP and PP from lake water samples. Results showed that orthophosphate (Ortho-P) constituted 32.4%–81.3% of DP and 43.7%–54.9% of PP, respectively; while monoester phosphorus (Mono-P) was 13.2%–54.0% of DP and 32.9%–43.7% of PP, respectively. Phosphorus in algae was mostly organic P, especially Mono-P, which was ≥50% of TP. Environmental factors and water quality parameters such as temperature (T), electrical conductivity (EC), pH, secchi depth (SD), dissolved oxygen (DO), chemical oxygen demand (CODcr ), chlorophyll-a (Chl-a), affected the absolute and relative concentrations of various P components in the two lakes. Increased temperature promoted bioavailable P (Ortho-P and Mono-P) release to the lake waters. The results can provide an important theoretical basis for the mutual conversion process of organic P components between various media in the lake water environment. Graphical abstract: Image 1 Highlights: Organic P was enriched by optimized flocculation in lakes and analyzed by 31 P NMR. Effects of environmental factors on organic P in various media were clarified. The processes of migration and transformation of organic P in lakes was analyzed. Ortho-P and Mono-P were up to 80% in eutrophic lakes. Algal biomass contains ≥50% organic P.